DISTRICT ROAD DATABASE MANAGEMENT BASED ON GEOGRAPHIC INFORMATION SYSTEM TO SUPPORT REGENCY ROAD MAINTENANCE (CASE STUDY: SINTANG DISTRICT) - Kurniawan, Yengkie; Widodo, Slamet (Jurnal Teknik Sipil, 2023)
Road maintenance on the section of the road classified as a district road in the Sintang sub-district is the responsibility of the Sintang District Government. The financial constraints of the Sintang District Government, allocated annually in the Regional Revenue and Expenditure Budget (APBD) of Sintang District, pose a challenge in realizing the plan for district road maintenance, whereas funding for road maintenance needs to be budgeted regularly to maintain the road conditions in good shape, therefore, in this case, stakeholders or decision-makers are expected to be able to consider and decide which road sections should receive recommendations for "urgent," "immediate," and "postponed" maintenance. The chosen road maintenance points must not solely prioritize the lowest construction costs, accessibility, or strategic area value. Indeed, in this case, an analysis is required to integrate various criteria, thus serving as the basis for a decision as the best choice. The research method is presented descriptively, explaining the determination of the scale for recommending maintenance of district roads. The data collection technique is carried out using primary data in the form of documentation photos of each road section and road condition data assessed using the Road Condition Index (RCI) method or road roughness index, as well as secondary data consisting of road inventory data, road condition data, accident data, area size data, socioeconomic data, and maps. The fulfillment of the Minimum Service Standards (MSS) for roads is then calculated based on the collected data. This includes both the MSS for individual road sections and the MSS for the road network. The fulfillment of the road network's MSS is divided into three aspects: accessibility, mobility, and safety. Based on the analysis of the MSS, it is categorized into three recommendations: "urgent," "immediate," and "postponed." After obtaining the recommendations for each road section, they are presented as a map. After obtaining the research results, two road sections fall under the "urgent" recommendation for road maintenance. For immediate recommendations, there are 15 road sections. Meanwhile, 44 road sections are included in the delayed recommendations for road maintenance to be carried out.